From DeWitt initial condition to cosmological quantum entanglement. (6th July 2015) - Davidson, A; Ygael, T
Abstract: At the classical level, a linear dilaton action offers an eternal inflation evolution governed by the unified (cosmological constant plus radiation) equation of state . At the quantum mechanical mini-superspace level, a 'two-particle' variant of the no-boundary proposal, notably 'one-particle' energy dependent, is encountered. While a (gravity–anti-gravity) GaG-odd wave function can only host a weak Big Bang (BB) boundary condition, albeit for any k, a strong BB boundary condition requires a GaG-even entangled wave function, and singles out k = 0 flat space. The locally maximal values for the cosmological scale factor a and the inverse Newton constant ϕ form a grid .